How video games impact players : the pitfalls and benefits of a gaming society - Rogers, Ryan (Lexington Books, 2016)
How Video Games Impact Players provides a balanced and nuanced look at the complex role that video games play in society through an analysis of the positive and negative effects of game rules, feedback, and self-presentation. Rogers examines the positive aspects of video games like their use in education, encouragement of prosocial behaviors, and enablement of mood management, as well as the negative aspects like their association with violence and diversity issues, promotion of substance use behaviors, and their role as an outlet for harassment behaviors. -- Publisher description.